2017
DOI: 10.1021/jacs.7b08896
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Formation of E- and Z-Disubstituted Double Bonds by Dehydratase Domains from Modules 1 and 2 of the Fostriecin Polyketide Synthase

Abstract: The dehydratase domain FosDH1 from module 1 of the fostriecin polyketide synthase (PKS) catalyzed the stereospecific interconversion of (3R)-3-hydroxybutyryl-FosACP1 (5) and (E)-2-butenoyl-FosACP1 (11), as established by a combination of direct LC-MS/MS and chiral GC-MS. FosDH1 did not act on either (3S)-3-hydroxybutyryl-FosACP1 (6) or (Z)-2-butenoyl-FosACP1 (12). FosKR2, the ketoreductase from module 2 of the fostriecin PKS that normally provides the natural substrate for FosDH2, was shown to catalyze the NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Recombinant FosDH1 was expressed and purified by procedures similar to those previously described. 24 Competent E. coli BL21(DE3) cells were transformed with the pET28a vector containing FosDH1 with codons optimized for expression in E. coli and the resultant recombinants were cultured under standard conditions. A single recombinant clone was inoculated into 10 ml LB medium containing 50 μg/ml kanamycin and grown at 37 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant FosDH1 was expressed and purified by procedures similar to those previously described. 24 Competent E. coli BL21(DE3) cells were transformed with the pET28a vector containing FosDH1 with codons optimized for expression in E. coli and the resultant recombinants were cultured under standard conditions. A single recombinant clone was inoculated into 10 ml LB medium containing 50 μg/ml kanamycin and grown at 37 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Although the observed p K a of an active site amino acid side chain can differ by 2–3 pH units from those of the corresponding free amino acids (and in one case an active site Asp has been reported to have a p K a > 9), 23 to date there has been no direct experimental evidence to support the requisite perturbations of the p K a of the active site Asp/Glu or His residues of any PKS or FAS dehydratase. Although some investigators have pointed out this apparent conundrum, 8, 24 to the best of our knowledge there have been no published studies of the pH dependence of any FAS dehydratase, and only a single determination of the pH rate profile for the k cat / K m of a PKS DH domain. 25 We now report that the pH-rate behavior of both k cat and k cat / K m of a prototypical PKS DH domain corresponds to a single ionization to an active basic form, consistent only with a single-base dehydration mechanism, and therefore inconsistent with an alternative base-acid mechanism requiring two pH-dependent ionizations.…”
mentioning
confidence: 99%
“…The DH domain generates a 2-enoyl thioester intermediate via syn -elimination of a 3-hydroxy group, resulting in the production of alkenes in even-to-odd positions in the final polyketide structure 19 . DHs are notable for a strict stereospecificity of the 3-hydroxy substrate, which has been correlated with the geometry of the product double bond 13,10 . Despite high-resolution crystal structures of several type-I PKS DHs, the structural basis for substrate specificity and product selectivity remains unclear 4, 1114 .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the modular borrelidin PKS, a DH domain creates a typical E -olefin, which is later isomerised 37 , while in the case of FR901464 a specialised TE domain rather than a DH domain, creates the Z -olefin 38 . In the case of the modular fostriecin PKS the DH from module 2 has been shown to create a Z -olefin directly 39 . Xie and Cane recently showed that in the cases of bongkrekic acid and oxazolomycin, produced by bacterial trans -AT PKS, a KR sets up a β-alcohol anti to an α-proton and the subsequent syn dehydration gives the Z -olefin directly 40 .…”
Section: Discussionmentioning
confidence: 99%